Analisis Strategi Brand Awareness (Top Of Mind, Brand Recall, Brand Recognition, Unaware Of Brand) Sepeda Motor Piaggio Vespa Di Jakarta - Rina Ayu Vildayanti (STIE Mandala Jember, 2019)
One of the most important thing of transportation is a motorcycle which is able to comply the level of people needs, because using a motorcycle can support various kinds of people activities to become more practical, economical and easy to drive.This research was intend to analyze the strategy of brand awareness Piaggio Vespa motorcycle in Jakarta, through elements Top of Mind, Brand Recall, Brand Recognition dan Unaware of Brand. The result of this study indicate that strategy of Brand Awareness Piaggio Vespa has been Top Of Mind which has made Piaggio Vespa the first scooter motorcycle to be caught by all respondents. Strategy of Brand Awareness Piaggio Vespa with Brand Recall approach, respondents stated that Piaggio Vespa is a type of scooter that is often heard whwn meeting friends or family. Meanwhile strategy of Brand Awareness Piaggio with Brand Recognition approach, respondents stated that Piaggio Vespa is a type of scooter that has good quality, proven technology and affordable price. Piaggio Vespa is not included by Unaware of Brand category.